Psychiatric Manifestations in Patients with Biopterin Defects - Parfyonov, Maksim; Friedlander, Robin; Banno, Brian; Elbe, Dean; Horvath, Gabriella (Neuropediatrics, 2022)
Psychiatric manifestations in patients with tetrahydrobiopterin (BH4) defects are common, and may occur even with treatment of the underlying disorder. The neurobiological background of these conditions has been linked to abnormalities of neurotransmitters, such as dopamine, serotonin, norepinephrine, and gamma-aminobutyric acid. Here, we review the psychiatric profile of all patients with BH4 defects followed in the pediatric and adult metabolic clinics at our center. Three patients with autosomal recessive (AR) guanosine triphosphate cyclohydrolase (GTPCH) deficiency and three patients with 6-pyruvoyl tetrahydropterin synthase (PTPS) deficiency were reviewed.All patients had behavioral disturbances and two had significant psychiatric comorbidities. These included attention deficit/hyperactivity disorder, anxiety, depression, aggression, or oppositional defiant disorder. One patient with PTPS deficiency had a severe psychiatric presentation, requiring inpatient admission and temporary placement into foster care for intensive behavioral therapy. Another with AR GTPCH deficiency was diagnosed with aggressive behavioral dysregulation requiring intensive psychiatric treatment. Management of the psychiatric manifestations of BH4 defects can be challenging, due to lack of information and studies of interactions between psychiatric medications on the deficient neurotransmitters and their receptors in these conditions. Further studies are needed to establish safety and efficacy of these treatments.
Keywords: inherited neurotransmitter disorders; tetrahydrobiopterin; levodopa/carbidopa